"Acting a play helped me." Year 8 students' understanding, inclusion and empowerment whilst using drama-focused collaborative learning to explore A Midsummer Night's Dream. (3rd April 2021) - Powell, Caroline
ABSTRACT: This case study examines the effects of collaborative, drama-focused activities on the cognitive understanding, social inclusion and empowerment of eight Year 8 students whilst studying A Midsummer Night's Dream . Each student chose a leadership responsibility throughout their five project-based research lessons, and the majority of students had additional needs. The participants were in a bottom set English class in a co-educational 11-18 academy, located in an East Anglian city. Tentative findings suggest that collaborative drama-focused activities supported the cognitive understanding and inclusion of participants. There was a notable increase in participants' perceptions of their own social inclusion and empowerment. The overall classroom ecology seemingly improved, and all participants with additional needs felt adequately supported. However, participants without additional needs still felt insufficiently supported. Factors such as low attendance and poor behaviour continued to negatively impact individuals' feelings of inclusion: this was exacerbated by the collaborative nature of research lessons.